Appscapes in everyday life: Studying Mobile Datafication from an Infrastructural User Perspective - Lai, Signe Sophus; Flensburg, Sofie (MedieKultur: Journal of media and communication research, 2020)
It has long been acknowledged that the use of ‘free’ mobile apps comes at a price, but few empirical studies have looked into this supposed trade-off. This article combines qualitative interviews with mappings of infrastructures for datafication in order to study the implications of mobile app usage from the perspective of individual users. It analyses users’ understanding of online tracking, maps the infrastructural tenets of mobile datafication, and finds a disconnect between what users believe happens to their data and the actua data harvesting and distribution mechanisms of their apps. We thereby argue that users’ resigned attitudes should be understood in light of the material conditions of the app economy and, as such, that user and infrastructure studies should join forces in exploring and enhancing users’ agency, empowerment and emancipation.